2014
DOI: 10.1007/s10709-014-9784-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic mapping of the Muller F element genes in Drosophila willistoni group

Abstract: Comparative genomics in Drosophila began in 1940, when Muller stated that the ancestral haploid karyotype of this genus is constituted by five acrocentric chromosomes and one dot chromosome, named A to F elements. In some species of the willistoni group such as Drosophila willistoni and D. insularis, the F element, instead of a dot chromosome, has been incorporated into the E element, forming chromosome III (E + F fusion). The aim of this study was to investigate the scope of the E + F fusion in the willistoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Others, such as dneb_sca_3, 6, and 10 all appear to constitute the D. willistoni chromosome 3 scaffold (Chr3). Consistent with these data, the genes eyeless ( ey ) and cubitus interruptus ( ci ), which are known to be located on chromosome 3 in D. nebulosa ( Pita et al 2014 ), can be found on scaffold dneb_sca_3 in our assembly. The X chromosome appears to be less contiguous with dneb_sca_2, 5, and 9 syntenic to the D. willistoni left arm (ChrXL), and dneb_sca_2, 4, 7, and 8 syntenic to the D. willistoni right arm (ChrXR1-4).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Others, such as dneb_sca_3, 6, and 10 all appear to constitute the D. willistoni chromosome 3 scaffold (Chr3). Consistent with these data, the genes eyeless ( ey ) and cubitus interruptus ( ci ), which are known to be located on chromosome 3 in D. nebulosa ( Pita et al 2014 ), can be found on scaffold dneb_sca_3 in our assembly. The X chromosome appears to be less contiguous with dneb_sca_2, 5, and 9 syntenic to the D. willistoni left arm (ChrXL), and dneb_sca_2, 4, 7, and 8 syntenic to the D. willistoni right arm (ChrXR1-4).…”
Section: Resultssupporting
confidence: 84%
“…In the several species of the willistoni group, the dot chromosome does not exist alone and is instead fused to chromosome 3 (fusion of Muller elements E + F). Previous studies have used fluorescence in situ hybridization to demonstrate that the ey , ci , and Ankyrin ( Ank) genes, which are present on chromosome 4 in D. melanogaster , are part of chromosome 3 in a number of species in the willistoni and bocainensis subgroups, D. willistoni and D. nebulosa included ( Papaceit and Juan 1998 ; Pita et al 2014 ). Hence, D. nebulosa has 3 chromosomes: X, 2, and 3; with the X and 2 consisting of a left and right arms ( Pavan 1946 ; Valente et al 1996 ; Schaeffer et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A dot chromosome is absent in D. willistoni , and chromosome III was hypothesized by Sturtevant and Novitski (1941) to have originated from the fusion of Muller elements E and F. Years later, Papaceit and Juan (1998) mapped three genes in D. willistoni by ISH, cubitus interrupitus ( ci ), ankyrin ( Ank ), and eyeless ( ey ), which are located in the D. melanogaster dot chromosome (Muller element F). They located the three genes in the centromeric region of D. willistoni chromosome III, corroborating with molecular techniques, the fusion of Muller elements E and F. This event has already been confirmed for all willistoni subgroup species ( Powell et al 2011 ; Pita et al 2014 ) with a timing of occurrence estimated at 15 Mya. In view of the good determination of the physical markers for the base of this chromosome we carried out an ISH with the gene Dwil\GK22422 located in scaffold 4921 ( Table S1 ), the most telomeric region.…”
Section: Resultssupporting
confidence: 69%
“…However, there are exceptions: In D . willistoni , the F element is fused to the E element (chromosome 3R in D. melanogaster ) ( Clayton and Wheeler 1975 ; Powell et al 2011 ; Pita et al 2014 ). In D. ananassae , the F element has expanded into a large metacentric chromosome of ≥ 18.7 Mb ( Schaeffer et al 2008 ; Leung et al 2017 ; Davis et al 2018 ).…”
Section: The Evolutionary History Of the F Element Within The Genus mentioning
confidence: 99%
“…Support for this finding comes from studies of species such as D. willistoni , D. busckii , and D. pseudoobscura . In D. willistoni , the F element was fused to Muller’s E element, one of the large autosomal arms ( Clayton and Wheeler 1975 ; Powell et al 2011 ; Pita et al 2014 ). When linkage disequilibrium, mutation rates, and recombination rates are compared between the F–E fusion chromosome in D. willistoni and the other chromosomes, no significant differences are found, in contrast to what is typically seen for the D. melanogaster F element ( Powell et al 2011 ).…”
Section: The Evolutionary History Of the F Element Within The Genus mentioning
confidence: 99%